2005
DOI: 10.1016/j.jada.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Soy Food Consumption in Women at Increased Risk for Breast Cancer

Abstract: ObjectivesThe objectives of the present study were to examine sociodemographic correlates of soy food con sumption among women at increased risk of breast can cer, describe factors influencing soy food consumption or nonconsumption, and identify women's sources of infor mation about soy foods. Design A cross-sectional, self-report survey was used to assess frequency of and factors influencing soy food con sumption. Soy food intake was reported for the past year. Subjects/setting Participants were 452 women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…In a previous analysis (12) we found that respondents to the SFQ were slightly older than nonrespondents (mean age = 42 vs. 41 yr) and more likely to be college educated (66% vs. 57%), but they were similar with respect to other demographic characteristics and health behaviors. We observed no significant differences in demographic characteristics or health behaviors, including isoflavone intake, between SFQ respondents (N = 451) and subsample subjects (N = 27).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In a previous analysis (12) we found that respondents to the SFQ were slightly older than nonrespondents (mean age = 42 vs. 41 yr) and more likely to be college educated (66% vs. 57%), but they were similar with respect to other demographic characteristics and health behaviors. We observed no significant differences in demographic characteristics or health behaviors, including isoflavone intake, between SFQ respondents (N = 451) and subsample subjects (N = 27).…”
Section: Discussionmentioning
confidence: 74%
“…Possibly, these women have controlled their soy intake as a result of concerns about the estrogenic effects of isoflavones. In a previous analysis, however, only 7% of nonconsumers wrote that they avoided soy foods for this reason (12). In our previous analysis, we found that not knowing how to prepare soy foods and disliking the taste of soy foods were the primary reasons for their nonconsumption (12).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Generally, GEN is developed and used as a protein tyrosine kinase inhibitor and an ER agonist to block PI3K/Akt activation. Nevertheless, with treatment of GEN, the level of phospho-Akt 308/473 expression in soloculture mammosphere cells does not differ according to our study, which means the inhibition of PI3K/Akt signaling by GEN in breast cancer is probably mediated by ER (30) or the concentration of GEN is not appropriate for suppression (45). Given that mammosphere cells from MDA-MB-231 cells lack ER and PR expression (46,47), GEN as a kind of phytoestrogen could not bind to ER to have antiproliferative effects by reduction of PI3K/Akt signaling.…”
Section: Discussionmentioning
confidence: 55%